Behavior and sex education in fourth course of compulsory secondary education (European Journal of Health Research, 2015)
Adolescence is a stage of life characterized by sexual development it causes in adolescents that they implement different sexual behaviors, which can be informed by a proper sexual education. This paper presents the results of a study on sexual behavior and sexual education of adolescents who completed the 4th year of secondary school in Murcia. The fundamental objectives pursued were focused on knowing how it was and how valued the sexual education that they receive, analyzing the different sexual behaviors that they performed and examining the knowledge regarding sexually transmitted diseases.  Participants in this study were a total of 112 students who answered a questionnaire. The results showed that 37.5% of participants had had coital sex, they had also done this for the first time at an average age of 15.1 years and having most used contraceptive methods.  The assessment made of sex education received was good, even though most knowledge they had was little or wrong.
Keywords: Adolescents; sexual education; sexual behavior; sexually transmitted diseases; contraceptive methods